Profile of Self-Regulated Learning and Argumentation Skills of Prospective Teacher Students Through Case Method Learning on Child Development Issues - Zuhrah Adminira Ruslan; Sugiarti; Muhammad Yunus (PT FORMOSA CENDEKIA GLOBAL, 2026)
Self-Regulated Learning and argumentation skills are important competencies that prospective teacher students must possess to face the demands of 21st-century learning. However, studies that describe these two competencies simultaneously in Case Method-based learning are still limited. This study aims to describe the profile of Self-Regulated Learning, argumentation skills, and learning outcomes of prospective teacher students through Case Method learning on child development issues. The study used a descriptive quantitative approach with 81 students taking the Child Development course in the 2025/2026 academic year using a total sampling technique. Data were collected through questionnaires on Self-Regulated Learning, argumentation skills, and Final Semester Exam (UAS) scores, which were then analyzed using descriptive statistics. The results showed that the majority of students had Self-Regulated Learning in the independent category (90.12%), argumentation skills in the high category (64.20%), and learning outcomes in the good category (61.73%). The results showed that Case Method learning was able to facilitate the development of Self-Regulated Learning, argumentation skills, and student learning outcomes. However, reinforcement through scaffolding, structured reflection, and evidence-based argumentation exercises is still needed to improve higher-order argumentation skills and encourage more students to reach the highest category.